An investigation of smoking habits and mental well‐being in healthcare personnel during COVID‐19. Issue 1 (30th April 2021) - Firat, Meryem; Demir Gökmen, Burcu; Karakurt, Papatya
Abstract: Aim: This study aimed to the smoking levels of the healthcare personnel ( n  = 761) in Turkey, the changes in their smoking levels, and their mental well‐being levels. Design and Methods: Data were collected via social networks from various cities in Turkey using a personal information form, the Fagerstrom test for nicotine dependence, the Warwick–Edinburgh mental well‐being scale. Findings: Their mean nicotine dependence score was 3.50 ± 2.57 and mental well‐being score was 25.01 ± 5.44. The frequency of smoking during the pandemic was increased in 22.4% of the participants and was the same as that before the pandemic in 57.4% of the smokers. Practice Implications: It is an introductory study of the current situation for healthcare professionals and researchers. It suggests protecting mental well‐being and reducing smoking.